Exercício físico como agente de prevenção e tratamento da sarcopenia - Santos, Bruna Cavalcante dos (Universidade Federal de São Carlos, 2024)
This work is a rigorous systematic review of scientific literature published in the past five years. The focus of the review is on the pivotal role of physical exercise in treating sarcopenia, a debilitating condition that is prevalent among the elderly. Sarcopenia is characterized by the gradual loss of muscle mass and strength, leading to reduced mobility, falls, fractures, metabolic disorders, and insulin resistance. The diagnosis of sarcopenia is determined through a range of methods, including the Dual-energy X-ray (DEXA) technique, which measures bone mineral density, muscle mass, and body fat. Another method is the European Working Group on Sarcopenia in Older People (EWGSOP) criteria, which includes handgrip strength and knee flexion/extension tests, are also used in the diagnosis. This review focuses on analyzing diverse modalities, intensities, and frequencies of physical exercise, with a key emphasis on resistance training. The review findings confirm that physical exercise, particularly resistance training, is a highly effective and promising approach to treating sarcopenia. The results demonstrate that physical exercise helps in maintaining muscle mass, improving muscle strength, and promoting mobility in the elderly. However, the review also highlights the need for future studies with larger samples and more refined methodologies to establish best practices and intervention periods, and to ascertain the efficacy of other exercise modalities in treating sarcopenia.
Physical exercise as an agent for the prevention and treatment of sarcopenia
Keywords: Exercício físico; Diagnóstico da sarcopenia; Sarcopenia; Treinamento resistido; Idosos; CIENCIAS DA SAUDE